Leading, managing, caring understanding leadership and management in health and social care - MacKian, Sara 1969-; Simons, Joan (Joan M.) (The Open University, 2013)
Effective leadership and management in health and social care are built on good practice, strong relationships and a critical understanding of the wider context in which care takes place. Leading, Managing, Caring illustrates how leadership and management work in everyday settings, providing invaluable support to those practising or studying in the area. The book introduces the four core building blocks of the caring manager or leader: personal awareness, team awareness, goal awareness and contextual awareness. Together these form a firm foundation for understanding and practice. Drawing on up-to-date case studies, the authors explore how critical theoretical understanding can support practical attempts to work through complex situations with a diverse range of people. Also included is a toolkit containing carefully selected and practical tools for leading and managing change. This comprehensive textbook is suitable for existing and aspiring managers and leaders in a range of health and social care professions, or anyone interested in understanding more about the complex landscape in which care services are managed and delivered in the UK. Show more Show les